1977
DOI: 10.1021/ac50014a015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 6-mercaptopurine in plasma by mass spectrometry

Abstract: A sensitive and specific method for the quantitative determination of 6-mercaptopurine In plasma Is described. A variety of techniques was used to eliminate endogenous material which may Interfere with the assay. The limit of detection of the method Is 20 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Detailed studies of azathioprine pharmacokinetics have now been conducted on renal transplant patients and these results will be reported elsewhere. Recently, Rosenfeld, Taguchi, Hillcoat & Kawal (1977) have developed a gas liquid chromatographymass spectrometric assay for 6-MP which seems to be specific although less sensitive than the present assay. The cost of instrumentation and personel however will limit its availability in clinical practice.…”
Section: Discussionmentioning
confidence: 85%
“…Detailed studies of azathioprine pharmacokinetics have now been conducted on renal transplant patients and these results will be reported elsewhere. Recently, Rosenfeld, Taguchi, Hillcoat & Kawal (1977) have developed a gas liquid chromatographymass spectrometric assay for 6-MP which seems to be specific although less sensitive than the present assay. The cost of instrumentation and personel however will limit its availability in clinical practice.…”
Section: Discussionmentioning
confidence: 85%
“…6-Mercaptopurine (6-MP) is an antineoplastic chemotherapy drug with a thiol group . Various methods have contributed much to the determination of 6-MP. Recently, it is found that the fluorescence of BSA–AuNCs can be selectively quenched by 6-MP over other thiol-containing compounds, such as glutathione and cysteine . Here, in order to evaluate the applicability and reliability of the proposed ERET sensor, it was applied for detecting 6-MP in human serum and urine samples.…”
Section: Resultsmentioning
confidence: 99%
“…6-Mercaptopurine (6-MP), a sulfur analogue of adenine, is one of the main ingredients of anti-neoplastic agents, and uses its toxic properties to suppress cancers such as acute lymphoblastic leukemia and inammatory bowel diseases. 1,2 Different analytical methods have been proposed for the analysis of 6-MP, such as chemiluminescence, 3,4 electrochemical methods, [5][6][7] high performance liquid chromatography (HPLC), [8][9][10][11] mass spectrometry, 12 capillary electrophoresis (CE) 13 Raman assays, 14 and electrochemical assays. 5,15 The electrochemical determination of 6-MP has limited application in real samples due to the poor repeatability and complex electrode modication process.…”
Section: Introductionmentioning
confidence: 99%